2004
DOI: 10.1161/01.cir.0000138849.03311.c6
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I Isoform Expression in Human and Experimental Atrial Fibrillation

Abstract: Background-Atrial fibrillation (AF) is accompanied by re-expression of fetal genes and activation of proteolytic enzymes. In this study both aspects were addressed with respect to troponin I (TnI) isoform expression. Methods and Results-Western blotting and real-time reverse transcription-polymerase chain reaction were used to study TnI isoform expression in patients with paroxysmal or chronic AF and in goats after 1, 2, 4, 8, and 16 weeks of AF. In addition to cardiac TnI (cTnI), low expression of slow-twitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…11 The predominant cTnI degradation product (cTnI 1 to 192 ) has been shown to significantly increase Ca 2ϩ sensitivity of human cardiac myofibrils. 14 However, in the present and previous studies 9,31 no changes in troponin content were observed and cTnI degradation products were undetectable in atrial samples from cAF patients.…”
Section: Interventions (High Extracellular [Ca 2ϩcontrasting
confidence: 51%
See 1 more Smart Citation
“…11 The predominant cTnI degradation product (cTnI 1 to 192 ) has been shown to significantly increase Ca 2ϩ sensitivity of human cardiac myofibrils. 14 However, in the present and previous studies 9,31 no changes in troponin content were observed and cTnI degradation products were undetectable in atrial samples from cAF patients.…”
Section: Interventions (High Extracellular [Ca 2ϩcontrasting
confidence: 51%
“…30 Although re-expression of ssTnI has been described in the early stages of AF in human atria and in a goat model of the disease, ssTnI was undetectable in atrial samples from patients with cAF. 31 A relation has been found in human atria between cAF and the activity of calpain-1, 32 a protease involved in degradation of contractile proteins, 33 including cTn. 34 Degradation of cTn by calpain has been reported to occur in both human cAF and a cell model for tachypacinginduced remodeling.…”
Section: Interventions (High Extracellular [Ca 2ϩmentioning
confidence: 99%
“…Using singlechannel bilayer recordings, Vest et al demonstrated an increased open probability of RyR2 channels isolated from dogs in persistent AF (4). This finding and the observation that RyR2 expression levels are unaltered or decreased in patients with chronic AF (33)(34)(35)(36) suggest that remodeling of the RyR2 macromolecular complex may underlie the defective channel function in chronic AF.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent focus on hormonal control of atrial electrophysiology, including genes controlling atrial natriuretic peptide levels and mineralocorticoid receptor expression, in patients with atrial fibrillation (Hodgson-Zingman et al, 2008;Roberts & Gollob, 2010;Tsai et al, 2010). Re-expression of dormant fetal genes may be one mechanism associated with the development of atrial fibrillation in adults, as was demonstrated by the appearance of the fetal ssTnI isoform of troponin in patients with atrial fibrillation (Thijssen et al, 2004). These changes could be primary causes of atrial fibrillation or may represent secondary changes related to other changes in myocardial metabolism, function or distension.…”
Section: Atrial Geneticsmentioning
confidence: 99%